2002
DOI: 10.1007/s003390201615
|View full text |Cite
|
Sign up to set email alerts
|

Yb-Yb correlations and crystal field in the Kondo-insulator YbB 12

Abstract: We have studied the effect of Lu substitution on the spin dynamics of the Kondo insulator YbB 12 to clarify the origin of the spin-gap response previously observed at low temperature in this material. Inelastic neutron spectra have been measured in Yb 1-x Lu x B 12 compounds for four Lu concentrations x = 0, 0.25, 0.90 and 1.0. The data indicate that the disruption of coherence on the Yb sublattice primarily affects the narrow peak structure occurring near 15-20 meV in pure YbB 12 , whereas the spin gap and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…1, the spectrum is dominated by a broad peak centred around 40 meV; whereas the components at 15 and 20 meV become undetectable. At T ¼ 160 K; the highest temperature of measurement, the Yb 0:1 Lu 0:9 B 12 spectrum resembles that of pure YbB 12 ; as found previously for Yb 0:75 Lu 0:25 B 12 [8]. Therefore, it can be inferred that the peaks at 15 and 20 meV; which become broadened, and eventually vanish, at low temperature upon substituting Lu for Yb, result from a coherent process requiring periodicity on the Yb sublattice.…”
Section: Recent Inelastic Neutron Scattering (Ins) Studiessupporting
confidence: 62%
See 1 more Smart Citation
“…1, the spectrum is dominated by a broad peak centred around 40 meV; whereas the components at 15 and 20 meV become undetectable. At T ¼ 160 K; the highest temperature of measurement, the Yb 0:1 Lu 0:9 B 12 spectrum resembles that of pure YbB 12 ; as found previously for Yb 0:75 Lu 0:25 B 12 [8]. Therefore, it can be inferred that the peaks at 15 and 20 meV; which become broadened, and eventually vanish, at low temperature upon substituting Lu for Yb, result from a coherent process requiring periodicity on the Yb sublattice.…”
Section: Recent Inelastic Neutron Scattering (Ins) Studiessupporting
confidence: 62%
“…Some of them [6] emphasize the role of Yb coherence in the formation of the gap state, whereas others [7] treat this factor as unimportant. In a previous INS experiment [8], we had studied the effect of coherence breakdown on the magnetic spectral response upon substitution of Lu for Yb. In a Yb 0:75 Lu 0:25 B 12 sample, the two near-gap peaks exhibited some broadening, almost without change in their integrated intensities.…”
Section: Recent Inelastic Neutron Scattering (Ins) Studiesmentioning
confidence: 99%
“…2. The 4f levels are split into G 6 ; G 7 and G 8 under the cubic symmetry with the energies E G6 oE G7 oE G8 : Under the hole picture, this is consistent with the crystal field levels E G6 > E G7 > E G8 suggested by the neutron scattering experiment [6].We found that the energy bands obtained by the LDA+U calculation can be fitted well by a simple tightbinding model with only the (dds) overlapping integral among the 5dE (xy; yz and zx) orbitals on Yb ions, and (dfs) between the 5d and 4f (J ¼ 7 2 ; G 8 ) states. This (dds) should be regarded as being produced by the effective hopping through the B 12 clusters.…”
mentioning
confidence: 53%
“…2. The 4f levels are split into G 6 ; G 7 and G 8 under the cubic symmetry with the energies E G6 oE G7 oE G8 : Under the hole picture, this is consistent with the crystal field levels E G6 > E G7 > E G8 suggested by the neutron scattering experiment [6].…”
mentioning
confidence: 62%